Nutrient cycling in an intercropped plantation of jacarandá-da-baía (Dalbergia nigra Fr. Allem.) with desmodium (Desmodium ovalifolium wall) - Corrêa, José Corulli; Corrêa, Ana Francisca Fernandes (Pesquisa Agropecuaria Brasileira, 1996)
A study was carried out to evaluate the nutrient cycling in an eight-year old plantation of jacarandá-da-baía (Dalbergia nigra Fr. Allem.) intercropped with desmodium (Desmodium ovalifolium Wall). Those cultures were cultivated in a clayey red yellow latosol of the Manaus region (AM), Brazil. Therefore, samples were collected from soil, litter of jacarandá and desmodium and phytobiomass of desmodium. The results indicated that the percentage of carbon, the nutrient contents (except P and Ca) and the physical properties of the soil were not significantly different between the treatments, although the litter was increased with the spacing of the jacarandá. The intercropped desmodium was benefitted by the P cycling utilized in the planting hole of jacarandá, though Ca contents in this soil were lower than in the areas cultivated only with desmodium.
Ciclagem de nutrientes em uma plantação de jacarandá-da-baía (Dalbergia nigra Fr. Allem.) consorciado com desmódio (Desmodium ovalifolium wall)